Effects of Intraoperative Lignocaine Infusion on Heamodynamics and Postoperative Analgesic Requirement after Day Case Laparoscopic Surgery - Shaheen, Md Shafiul Alam; Sardar, Kawsar; Khatun, U H Shahera; Rahman, Md Mushfiqur; Ahmed, Raju; Abbasi, Md Mahmud (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background:Intravenous lignocaine is an amide local anaesthetic known for its analgesic, anti-hyperalgesic, anti-inflammatory and anti-arrhythmic properties. During perioperative period of laparoscopic surgeries haemodynamic alteration occurs due to laryngoscopy, intubation, and surgical excision, gas insufflation during pneumoperitoneum, inadequate analgesia and inadequate depth of anaesthesia. Intravenous lignocaine is often administered to suppress the haemodynamic response and as an analgesic agent. We aimed to evaluate the effect of intravenous infusion of lignocaine on haemodynamic response and post-operative analgesic requirement. Objectives:The purpose of this study was to evaluate the effect of intravenous infusion of lignocaine on haemodynamic and postoperative analgesic requirements after laparoscopic day case surgeries. Material and method:Four hundred Sixty (460) patients were selected who’s were going to be operated for laparoscopic surgeries (Laparoscopic Cholecystectomy, laparoscopic Hernioplasty, laparoscopic appendicectomy, Diagnostic laparoscopy due to infertility) were grouped into exposed (Group L) who were received lignocaine infusion @1mg/kg/hr and controlled (Group C) who were received placebo. Systematic random sampling was employed. Results:Demographic characteristics were comparable between the groups p>0.05. In lignocaine group intraoperative mean systolic blood pressure, mean diastolic blood pressure, mean arterial blood pressure and mean heart rate were significantly lower than control group (p<0.05). Twenty four hour mean VAS score (0 – 10 cm) at immediate recovery, 1st, 2nd, 3rd, 6th, 12th and 24th hour were lower in lignocaine group (p<0.05). The mean time of first analgesic requirement were longer (120 minutes) in lignocaine group compared to 40 minutes in control group (p<0.001) and the mean total tramadol consumption is less in lignocaine group (p<0.001). Conclusion:Intra operative lignocaine infusion causes more haemodynamic stability and decreases postoperative pain score, required longer time for first analgesic requirement and reduced total analgesic consumption in laparoscopic surgeries. J Bangladesh Coll Phys Surg 2024; 42: 312-320